2022
DOI: 10.1039/d1sm01816g
|View full text |Cite
|
Sign up to set email alerts
|

Motion of an active particle with dynamical disorder

Abstract: We propose a model for the motion of a single active particle in a heterogeneous environment where the heterogeneity may arise due to the crowding, conformational fluctuations and/or slow rearrangement...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 83 publications
0
14
0
Order By: Relevance
“…Recently, a number of experimental and theoretical studies have been carried out to investigate the dynamics of selfpropelled species in crowded and complex environments. [17][18][19][20][21][22][23][24][25][26] Recent experimental and theoretical studies reported enhanced rotation of a self-propelled Janus particle in a polymer solution. 6,22,27 Most of the previous attempts focused on the effect of crowding on dynamics by changing the nature and density of the crowders.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a number of experimental and theoretical studies have been carried out to investigate the dynamics of selfpropelled species in crowded and complex environments. [17][18][19][20][21][22][23][24][25][26] Recent experimental and theoretical studies reported enhanced rotation of a self-propelled Janus particle in a polymer solution. 6,22,27 Most of the previous attempts focused on the effect of crowding on dynamics by changing the nature and density of the crowders.…”
Section: Introductionmentioning
confidence: 99%
“…Several models with both the memory effect and the fluctuating diffusivity have been proposed and studied so far [5,6,[25][26][27][28][29], but physical backgrounds of these models, such as the fluctuation-dissipation relation, have been unclear. In this paper, we proposed the GLEFD [Eq.…”
Section: Discussionmentioning
confidence: 99%
“…Thus it is important to incorporate the fluctuating diffusivity into diffusion processes with a memory effect such as the GLE. In fact, to describe the diffusion process observed in complex media such as the cytoplasm, phenomenological models which combine these two effects have recently been proposed and studied [5,6,[25][26][27][28][29]. However, physical backgrounds of these phenomenological models have been still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the motion of passive particles is governed by equilibrium thermal fluctuations owing to random collisions with the surrounding fluid molecules, while the active particles are driven by the interplay between random fluctuations and self-propulsion that drives them out of equilibrium . To describe the motion of active particles, researchers have proposed different models, such as active Brownian particles, , active Ornstein–Uhlenbeck particles, , and run and tumble particles . The dynamics of active Brownian particles become the central focus of the physical and biophysical research communities.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamics of active Brownian particles become the central focus of the physical and biophysical research communities. In the last few decades, several studies are reported, which try to reveal the physics behind the novel features exhibited by the active Brownian particles in complex media. , However, the real-life situations are quite different, and hence there is a growing interest in understanding the dynamics of these active Brownian particles in complex environments such as porous soils, sediments, and living tissues. There are multiple factors like crowding and local heterogeneity that either enhance or limit the diffusion of active agents moving through these complex media for performing their assigned tasks.…”
Section: Introductionmentioning
confidence: 99%